From Raw Emotions to Narrative Transformations: A Psychoanalytic Interpretation of the Horse Trope in Gianna Manzini’s Narrative - Sergi, Maria (Spunti e Ricerche, 2016)
This article advances the argument that Gianna Manzini’s oeuvre is best appreciated as an overarching autobiographical text in which the subject is not a pre-determined simulation drawn from memory. I argue, rather, that the aesthetics of her subjects’ constant coming-into-being throughout her writing constitutes an over-arching autobiographical account. The horse is one of Manzini’s recurring narrative tropes. I explore the evolution of the horse character through the psychoanalytic lens of Antonino Ferro’s theory of “narrative derivatives”, which are understood to sponsor “narrative transformations”. I examine four horse characters drawn from four separate stories and argue that they contain and reflect hitherto unrecognised traumatic responses embedded in her father’s memory. I argue that in this way she accomplishes a narrative transformation of previously mute traumata.